Health-related quality of life and functional outcome measures for pediatric multiple injury: A systematic review and narrative synthesis. Issue 5 (2nd May 2022) - Collins, Kathryn C.; Burdall, Oliver; Kassam, Jamila; Firth, Gregory; Perry, Daniel; Ramachandran, Manoj
Abstract : This systematic review identifies the current outcome measures used in paediatric polytrauma. The findings provide the basis for the development of a core outcome set to better understand the impact of poly-trauma on children and as they grow and develop over their life. Abstract : BACKGROUND: Pediatric multiple injury is a major cause of mortality and morbidity worldwide, with varied long-term sequelae. To improve care, a better understanding of the outcome tools used following multiple injury is needed. OBJECTIVES: This study aimed to (1) identify the outcome tools used to assess functional and health-related quality of life outcomes in pediatric multiple injury and to (2) describe the tool domains and validity. METHODS: Eligible studies were those that included pediatric participants aged 0 to 17 years who experienced multiple injury or severe trauma based on Injury Severity Score/Abbreviated Injury Scale score and a functional outcome tool was used to assess outcomes (e.g., physical, psychological, quality of life). Excluded study designs were editorials, narrative, and systematic reviews. RESULTS: Twenty-two papers were included encompassing 16, 905 participants and 34 different outcome tools. Ten tools were validated in children of which 4 were multiple injury specific; 18 were validated in adults of which 8 were trauma specific, and 6 were previously unvalidated. The tools were a mixture of patient reported (7 of 10 validated in children and 13 of 18 validated in adults) and clinician reported (3 of 10 validated in children and 2 of 13 validated in adults). Pediatric tool domains assessed were function, mobility, activities of daily living, pain, school, cognition, emotional domains, mental health, behavior, and high-risk behaviors. Using adult-validated tools to assess children may not capture the children's true function and health-related quality of life. CONCLUSION: There was a lack of consistency in the outcome tools used following multiple injury in children. Adult-validated measures may not accurately capture pediatric outcomes after multiple injury. To fully understand the impact of pediatric multiple injury and make comparisons between studies, development of a core outcome set is required. LEVEL OF EVIDENCE: Quantitative observational studies, level III.